Adaptive Policy in Website-Based Digitization of Government Public Services: A Thematic Analysis - Fisdian Adni, Dita; Rusadi, Sylvina; Baharuddin, Tawakkal (Universitas Muhammadiyah Malang, 2024)
Digital-based public services have an essential urgency in increasing efficiency, accessibility, transparency, and responsiveness of services to the public. This allows for significant improvements in governance. This research aims to analyze the implementation of services by local governments, especially at the One Stop Integrated Services Investment Service (DPMPTSP) of Rokan Hilir Regency. This research uses a qualitative approach using Online Research Methods (ORMs) as a data collection method. ORMs utilize the internet and other digital technologies to collect data and information. In this research, ORMs include data collection from official government websites. The analysis tool that is maximized is Nvivo 12 Plus. This research shows that implementing website-based digital public services faces obstacles and challenges that need to be overcome. Limited internet access, technology gaps, concerns regarding security and privacy, and limited resources are the primary concerns. However, the government can overcome these obstacles by investing in internet infrastructure, digital literacy programs, and collaboration with the private sector. Integrating digital public services can increase the efficiency, accessibility, transparency, and accountability of public services and build public trust in the government. In facing this challenge, the government needs to take appropriate policy steps to ensure the success and sustainability of inclusive and sustainable digital public services.